Endoscopic unilateral transethmoid‐paraseptal approach to the central skull base. Issue 5 (28th May 2017) - Eördögh, Márton; Briner, Hans Rudolf; Simmen, Daniel; Jones, Nicholas; Reisch, Robert
Abstract : Objectives: The endoscopic technique in transnasal skull base surgery offers optimal visualization and free manipulation in the surgical field. However, it may cause approach‐related sinonasal injury, influencing patients' quality of life (QOL). To minimize rhinological morbidity without restrictions in surgical manipulation and tumor resection, we introduced the unilateral transethmoidal‐paraseptal approach. In this article, we analyzed the long‐term results and sinonasal outcome of this technique. Study Design: Retrospective analysis of medical records. Methods: Forty‐two consecutive patients underwent surgery between June 2010 and March 2014 using the transethmoid‐paraseptal approach. Perioperative work‐up included neurological, radiological, endocrinological, ophthalmological, and rhinological analysis. Patients' preoperative, 1‐month and 1‐year postoperative QOL was measured using the Sino‐Nasal Outcome Test (SNOT‐22). Results: At all individuals, a unilateral transethmoid‐paraseptal approach was performed. Removal of the turbinates, posterior septal resection or a conversion to biportal surgery could be avoided in all cases. There were no intraoperative neurovascular complications. All patients had a notable improvement in any disease‐related symptoms, as well as by objective criteria. Complete tumor resection was aimed in 39 cases and achieved in 31 of them. The SNOT‐22 scores transiently worsened 1 month after surgery and non‐significantly improved after 1 year, compared with the preoperative status. A subgroup of 7 patients with preoperative sinonasal disease evidence showed continuous significant improvement (p < .05) of SNOT‐22 scores across time. The smell screening tests showed no significant difference across time. Conclusion: The described approach allows safe removal of various skull base lesions without deterioration in sinonasal QOL and smell function. Level of Evidence: 4.